(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
The main purpose of this study was to examine the role of counselling on the mental health of survivors of extrajudicial executions in the Mathare informal settlement of Nairobi. For the realization of this research aim, the study was guided by four specific objectives. These objectives comprised to examine the prevalence of mental illnesses and disturbances among the survivors of extrajudicial executions in Mathare Informal Settlement; to identify the key problems leading to mental health complications in Mathare Informal Settlement; to determine the contribution of counselling on the mental health of survivors of extrajudicial execution in Mathare Informal Settlement; to identify possible obstacles that prevent survivors of extrajudicial execution in Mathare Informal Settlement from accessing and utilizing counselling services. The research design and methodology used were ex post facto and mixed methodology, respectively. Data collection was done using questionnaires, whereas for descriptive analysis, SPSS (statistical package for social sciences) was used. The study also utilized measures of central tendency such as mean, mode, tables, and frequencies. After the data analysis process, the study found that counselling positively impacted the extrajudicial execution survivors’ mental and general wellbeing, thus concluding that a significant relationship existed between counselling services and the extrajudicial execution survivors’ mental health.